Role of Metallic Nanoparticles in Vaccinology: Implications for Infectious Disease Vaccine Development - Marques Neto, Lázaro Moreira; Kipnis, André; Junqueira-Kipnis, Ana Paula (Frontiers in Immunology, 2017)
Subunit vaccines are safer but less immunogenic than live-attenuated vaccines or whole cell inactivated vaccines. Adjuvants are used to enhance and modulate antigen immunogenicity, aiming to induce a protective and long lasting immune response. Several molecules and formulations have been studied for their adjuvanticity, but only six have been approved to formulate human vaccines. Metallic nanoparticles (MeNPs), particularly those containing gold and iron oxides, are widely used in medicine for diagnosis and therapy and have been used as carriers for drugs and vaccines. However, little is known about the immune response elicited by MeNPs or about their importance in the development of new vaccines. There is evidence that these particles display adjuvant characteristics, promoting cell recruitment, antigen presenting cell activation, cytokine production, and inducing a humoral immune response. This review focuses on the characteristics of MeNPs that could facilitate the induction of a cellular immune response, particularly T-helper 1 (Th1) and Th17, and their potential functions as adjuvants for subunit vaccines.